Manipulative media KOBI (Kartu Operasi Bilangan Integrasi) to improving creative thinking abilities - Putri Dwi Arianti; Taufiq Satria Mukti; Faridah Hanim Binti Yahya; Ilham Imtiyazil Ilmi; Muhammad Iqbal Rifqy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Learning mathematics requires appropriate learning media. The facts in the field of learning are textbook and monotonous. Kartu Operasi Bilangan (KOBI) is a manipulative media developed through game-based methods Teams Games Turnament (TGT). This media is used to support the learning process of students in the classroom both individually and in groups. The purpose of this research is to determine the effectiveness of the KOBI media in enhancing students' creative thinking abilities. The study was conducted on 7th-grade students at MTsN 7 Malang, focusing on the topic of integers. The research utilized a quantitative approach through quasi-experimental methods. Data collection involved tests, questionnaires, and direct observations during the learning sessions. The research findings concluded that the KOBI media is effective in supporting the learning process to enhance students' creative thinking abilities